3D printing: Development of animal products and special foods. (December 2021) - Bhat, Zuhaib F.; Morton, James D.; Kumar, Sunil; Bhat, Hina F.; Aadil, Rana Muhammad; Bekhit, Alaa El-Din A.
Abstract: Background: The present review examines the printing properties of different animal protein-based food inks/materials used in the production of 3D printed constructs. The review examines their microstructural, colorimetric, printability, rheological and textural properties and investigates how these properties correlate to or are reflected in the characteristics of the printed constructs. These characteristics include their shape and dimensional stability, textural, nutritional, microstructural and sensorial properties. The review also examines the potential for development of animal protein-based special diets for people with special requirements such as for dysphagia patients and geriatrics. A special focus has been given to the application of transglutaminase for the development of 3D fish-based products and the possibility of developing cultured meat-based products. Scope and approach: The properties of different food inks and 3D printed constructs based on animal proteins such as beef, poultry, fish, egg, seafood, milk, cheese and dairy ingredients were analysed with emphasis on the studies that were published in the last three years. Studies on the development of special animal protein-based diets and the possibility of 3D printed products based on cultured meat were critically reviewed. Key findings and conclusions: 3D food printing offers numerous possibilities for development of tailored animal protein-based structures and products which includes, but is not limited to, extraordinary flexibility in geometries, textures and flavours and customised nutrition. Technology for production of 3D printed meat products necessitates the reduction of particle size of meat and dilution of meaty and savoury flavour and this is generally expected to reduce the value of premium meat products. However, the technology might be a good option for utilization of lower value and tougher cuts and trimmings. Production of 3D printed cultured meat-based products is still at a conceptual stage and a little or no research has been done in this area. Consumer acceptance of 3D printed cultured meat products seems to be less favourable in Western countries like Australia. Technology for the production of several animal protein-based 3D printed products for special dietary requirements such as for dysphagia patients has been optimized and is currently feasible with good success. Fancy shaped 3D printed cheese and egg products may evolve as a new segment of foods with a focus on children, festive occasions and the personal gift market. This review expands our understanding of how the composition of food inks affects the properties of the printed constructs and generates knowledge that will be crucial for optimizing the 3D printed animal products for maximum nutritional and sensory benefits. Extensive research is required to develop unique animal-based products with functional and nutraceutical value to attract consumers. Scientific knowledge is required to decipher the underlying mechanisms of how 3D printing process affects the food microstructure and sensory characteristics and its impact on consumer acceptance that will expand the use of the technology within the food industry. Highlights: 3D food printing offers numerous possibilities for development of tailored animal protein-based products. This technology might be a good option for utilization of lower value and tougher cuts of meat. Production of 3D printed cultured meat-based products is still at a conceptual stage. Production of the products for special dietary requirements is feasible with good success. Fancy shaped 3D printed cheese and egg products may evolve as a new segment of foods.